An Analysis of Themes in The Casher Short Story by John Collier - Laksmiari, I Gusti Ayu; Mulyana, Novita; Ediwan, I Nyoman Tri; Utami, Gek Wulan Novi (IAI Nasional Laa Roiba Bogor, 2024)
The study examines the theme of “The Chaser” a short story by John Collier.